Gestation and prediction of whelping in the bitch - Sánchez R., Alfonso (2017)
The pregnancy in the bitch occurs between fertilization and whelping, and its length has clinical importance. The complex biology of the gametes and embryos influences the length of the gestation, where the physiological period fluctuates from 57 to 70 days. This wide range can be influenced by the referential methods used to estimate the starting day. Controlled natural mating or artificial insemination based on the detection of ovulation allows reducing the range from 62 to 64 days. A high impact obstetric condition is the gestation of only one puppy, which tends to be longer, representing high risk of dystocia. Given the clinical relevance of a suitable projection of the length of the gestation and the prediction of the whelping date, mathematical formulas to calculate the fetal age and the whelping day have been developed with the systematization of gestational ultrasound.